Stable Isotope Analysis of Juvenile White Sharks Inside a Nursery Area Reveals Foraging in Demersal-Inshore Habitats and Trophic Overlap With Sympatric Sharks - García-Rodríguez, Emiliano; Herzka, Sharon Z.; Sosa-Nishizaki, Oscar; Lowe, Christopher G.; O’Sullivan, John B. (Frontiers in Marine Science, 2021)
Knowledge about top predators' trophic ecology is crucial for defining their role in ecosystems, understanding habitat preferences, characterizing life stage-specific feeding habits, and evaluating their interaction with fisheries. In the northeastern Pacific, white sharks (Carcharodon carcharias) occupy coastal habitats during the early life stages, including Bahía Sebastián Vizcaíno (BSV) in Mexico, which is a known nursery area. Although BSV presumably provides high prey abundance, the trophic ecology of immature white sharks is poorly understood. Carbon and nitrogen bulk stable isotope analyses (SIA) were used to explore the trophic relationship of early life stages with their potential prey and to infer dietary overlap with sympatric sharks, while SIA of amino acids were used to estimate trophic position. Muscle samples from young white sharks and inshore demersal prey commonly found in their stomach contents were sampled. Demersal prey and literature-derived isotope ratios for pelagic and offshore species were incorporated into mixing models with a Bayesian framework to estimate their contribution to white shark tissues. Nearshore demersal prey had the highest contribution for all life stages (between 35-47%), consistent with previous reports based on gut content analysis. The contribution of pelagic (between 26-37%) and offshore (between 14-32%) prey was smaller and suggests potential periodic changes in foraging grounds and the presence of a maternal-derived isotopic signature. A high contribution of demersal prey indicates a high level of interaction with local fisheries that target those species and catch white sharks incidentally and is consistent with immature shark movement patterns. Isotope ratios of two sympatric sharks, smooth hammerhead Sphyrna zygaena and copper sharks Carcharhinus brachyurus, were used to estimate the overlap in isotopic niche space. Immature white sharks had the smallest isotopic niche, while the highest was for copper sharks. Overlap was greatest between white sharks and hammerheads (~45%), while overlap with copper sharks was limited (<20%), suggesting less potential for competition. Trophic position estimates were similar to those previously reported for the species. These results highlight the importance of coastal demersal prey heavily targeted by local fisheries for the diet of young white sharks and support the importance of BSV as a nursery habitat.